Causal impacts of 731 immunocyte phenotypes on colorectal cancer-evidence from a bidirectional two-sample Mendelian randomization - Xinyue Gu; Shihui Zhao; Mingyu Xia; Songtao Du; Liqiang Song; Tianyi Xia; Bomiao Zhang (Taylor & Francis Group, 2024)
Colorectal cancer is one of the most common and lethal malignancies, and various factors have been confirmed to contribute to its occurrence. However, the causal role of immune cell-specific changes in the development of colorectal cancer has not been investigated. The bidirectional two-sample Mendelian randomization analysis was performed to explore the association between 731 types of immune cell phenotypes-specific changes and colorectal cancer. The inverse variance weighting results indicated that a total of 31 and 28 immune cell phenotypes significantly associated with colorectal cancer in two different datasets, respectively. The primary results of inverse variance weighting Mendelian randomization suggested that the immune cell phenotypes BAFF-R on IgD+ CD38dim (OR = 1.033, 95%CI: 1.005-1.062) and SSC-A on monocyte (OR = 1.055, 95%CI: 1.016-1.096) served as risk factor for colorectal cancer. In addition, the meta-analysis further supports the causal link of BAFF-R on IgD+ CD38dim (pooled OR = 1.035, 95%CI: 1.013-1.059) and SSC-A on monocyte (pooled OR = 1.060, 95%CI: 1.026-1.095) with colorectal cancer. Finally, the inverse variance weighting Mendelian randomization result suggested that genetic determinants of colorectal cancer may decrease the level of HLA DR++ monocyte absolute count (OR = 0.686, 95%CI: 0.508-0.925). Our results indicated that the potential causal association of BAFF-R on IgD+ CD38dim and SSC-A on monocyte with colorectal cancer. The identified immune cells may be appealing drug targets for colorectal cancer, but lack confirmation from real clinical evidence. Further studies are needed to investigate the roles of these immune cells in colorectal cancer.